-(1/9)(x-27)+(1/3)=x-59

Simple and best practice solution for -(1/9)(x-27)+(1/3)=x-59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(1/9)(x-27)+(1/3)=x-59 equation:


x in (-oo:+oo)

1/3-((1/9)*(x-27)) = x-59 // - x-59

1/3-((1/9)*(x-27))-x+59 = 0

(-1/9)*(x-27)-x+1/3+59 = 0

1/3-1/9*(x-27)-x+59 = 0

(-1/9*3*(x-27))/3+(3*(-x))/3+1/3+(3*59)/3 = 0

3*(-x)-1/9*3*(x-27)+3*59+1 = 0

1-10/3*x+9+177 = 0

10-10/3*x+177 = 0

187-10/3*x = 0

(187-10/3*x)/3 = 0

(187-10/3*x)/3 = 0 // * 3

187-10/3*x = 0

187-10/3*x = 0 // - 187

-10/3*x = -187 // : -10/3

x = -187/(-10/3)

x = 561/10

x = 561/10

See similar equations:

| (6x-4)(7x-5)=0 | | -2.5a+1.33333+.6666667=3.25 | | -14x-5x=15+55 | | (1/3)(5x+3)-(1/4)(x+5)=4 | | 175=50t | | 3x+38=5x-12 | | 2.6666667r-2.25r=.4166667 | | c=y+b | | (5+3i)-(2+xi)=3-7i | | (1/5)(x-4)=4x-3(x-1)+(13/5) | | .75x+1.5=1.833333 | | 10-2x=20-4x | | x+1-2x=x-3+x-8 | | 4(3x-5)-2x=5x+10 | | (5y^4+2x^3y)dx-(4xy^3+x^4)dy=0 | | 2(5+a)= | | -10x-5+4x=-4+3 | | 15-3x=47-11x | | r=w-b(2c+b) | | r-3.3333333+.5=-1.83333 | | a+5=-5a-7 | | 8x^2-27y^3=0 | | 4+13+72+89-100+200-1534+7= | | 8y+4=7y-1 | | (1/5)(x+4)=6x-3(1-x)-5 | | 3x/x+6=0 | | 15+2x=69-4x | | 1-k=-8-k+3k | | -8=4-x | | n+m=20 | | 100-4x=16+3x | | -2r+.33333333-2.5r=-4.166667 |

Equations solver categories